The Clash Of Property And Environmental Rights In The Niger Delta Region Of Nigeria - Lugard, Sunday Bontur (Journal of Sustainable Development Law and Policy, 2025)
The Niger Delta region of Nigeria, home to about 30 million people, is one ofthe world’s most prominent deltas. Petroleum exploration in this region hasbeen ongoing for over fifty years and revenue from this activity is at presentthe mainstay of the Nigerian economy. Granted that it is impracticable toundertake petroleum operations without some negative impact on theenvironment, a good deal of this pollution can be mitigated. The InternationalOil Companies (IOCs) are complacent about pollution reduction to asustainable level; regulatory agencies are either compromised or lack therequired expertise or equipment to monitor and enforce compliance withextant environmental protection laws and regulations. The pursuit of theIOCs’ property right over petroleum resources has set them against the otherstakeholders’ right to a healthy environment. The clash of these rights canbest be addressed by ascribing “collective property” and not “private property”right to the acreage over which they have been granted licence to prospectfor, explore or mine petroleum resources.